Prototypical analysis of social representations of depression among elderly women - Camelo, Lana Carine Soares Dias (2023)
This study aimed to apprehend the social representations of depression among elderly women. 64 elderly women participated in the research, divided into two groups, with a mean age of 68.6 years (SD=7.2) and 68.5 (SD=8). The free word association technique was used, with data analyzed through prototypical analysis using the Iramuteq software. The results pointed to a positive SR of aging for the group of elderly women participating in conviviality groups for elderly people and negative for elderly women who did not participate in groups. The SR of depression were equivalent in both groups. In conclusion, the necessity and importance of permanent health education about depression was identified, focusing mainly on elderly women as a target audience.